Neuropsychological Factors Related to College Ice Hockey Concussions. (May 2014) - Pedersen, Heather A.; Ferraro, F. Richard; Himle, Michael; Schultz, Caitlin; Poolman, Mark
We analyzed data from 74 male collegiate hockey players. Each athlete's season began with a baseline administration of the Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT) neuropsychology test battery. Fourteen athletes sustained a sport-related head injury and were readministered the test to assess the impact of the injury. A significant decrease in performance (compared to baseline) on immediate and delayed word recall and designs followed the first concussion. Following a second sport-related concussion, the 4 affected athletes showed significant decrease in visual motor speed. Performance improved on 2 response speed measures ( P s < .01). More errors occurred during a visual processing/discrimination task and immediate recall of designs declined ( P s < .05). We discuss the results in light of recent work related to the impact of early-life concussions and head injury on late-life consequences, such as chronic traumatic encephalopathy, and more immediate issues such as return-to-play decisions for athletes.